THE ROLE OF MARKETING MANAGEMENT IN IMPROVING SERVICES AT J&T EXPRESS DP02 DURIAN 3 IN BERAU DISTRICT - Imam, Agus (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
The Role of Marketing Management in Increasing Service Users at J&T Express DP02 Durian 3 in Berau Regency. The purpose of the research conducted was to find out and analyze the role of marketing management in increasing service users at J&T Express DP02 Durian 3 in Berau Regency. The research was conducted on 3 J&T Express employees and 8 J&T Express consumers as samples. Based on the results of the research, it can be seen that the marketing management team at J&T Express has carried out its role well. This can be seen from the preparations of the plans carried out at the beginning of the year, which were then socialized to each J&T Express branch to take action in each respective area. However, from here the central marketing management team continues to monitor the progress of the plan and measure the success of the plan by looking at the increase in the number of consumers. If the plans drawn up are not successful, the marketing management team will carry out an evaluation.